The effect of virtual community for physical activity on student's physical activity in the era of pandemic Covid-19 - Imas Damayanti; Adi Gustira (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2021)
The purpose of this study was to increase the physical activity of students in the era of the COVID-19 pandemic, to maintain and improve body fitness. A quantitative approach using the experimental design method then with a one - group pretest - posttest design research design. Then the population in this study were UPI students in semesters 2-3, who had low physical activity. with a sample of 12 female students. This research was conducted during the first month of the first week for the pre-test, then the 2nd and 3rd weeks for treatment and ended with the post test for the 4th week, the data was collected using the accelerometer actgraph instrument and the Global Physical Activity Questionnaire (GPAQ). The results of the mets value for the pretest 1.153 to 1.27 for the post-test score, for the average total stepcount value for the pretest 2. 619 to 3340, while the mets value for the pretest GPAQ was 432.67 and then for the posttest value 529.58. The conclusion is that there is a significant influence from the virtual community for physical activity on the physical activity of students during the Covid-19 pandemic.Pengaruh virtual community for physical activity terhadap aktivitas fisik mahasiswa di era pandemi Covid-19AbstrakPenelitian ini adalah untuk meningkatkan aktivitas fisik mahasiswa di era pandemi covid -19, untuk menjaga dan meningkatkan kebugaran tubuh. Pendekatan penelitian adalah penelitian kuantitatif dengan metode eksperimen desain one - group pretest - posttest design. Sampel pada penelitian ini adalah mahasiswi UPI semester 2 sampai dengan 3 yang mempunyai aktivitas fisik rendah. Penelitian ini dilaksanakan selama satu bulan, minggu pertama untuk pre-test, lalu minggu ke 2 dan 3 untuk perlakuan dan diakhiri dengan post-test untuk pada minggu ke-4. Instrumen pengambilan data yang digunakan diantaranya accelerometer actigraph dan Global Physical Activity Questionnaire (GPAQ). Hasil dari nilai mets untuk pretest 1,153 menjadi dan meningkat menjadi 1,27 pada akhir perlakuan. Nilai stepcount total rata rata pretest 2619 meningkat menjadi 3340, dan nilai mets pada GPAQ pretest 432.67 meningkat menjadi 529.58. Kesimpulan penelitian ini bahwa terdapat pengaruh yang signifikan dari virtual community for phisical activity terhadap aktivitas fisik mahasiswa pada era pandemi Covid-19